The epidemiology of sepsis in Brazilian intensive care units (the Sepsis PREvalence Assessment Database, SPREAD): an observational study. Issue 11 (November 2017) - Machado, Flavia R; Cavalcanti, Alexandre Biasi; Bozza, Fernando Augusto; Ferreira, Elaine M; Angotti Carrara, Fernanda Sousa; Sousa, Juliana Lubarino; Caixeta, Noemi; Salomao, Reinaldo; Angus, Derek C; Pontes Azevedo, Luciano Cesar; ,; ,
Summary: Background: The sepsis burden on acute care services in middle-income countries is a cause for concern. We estimated incidence, prevalence, and mortality of sepsis in adult Brazilian intensive care units (ICUs) and association of ICU organisational factors with outcome. Methods: We did a 1-day point prevalence study with follow-up of patients in ICU with sepsis in a nationally representative pseudo-random sample. We produced a sampling frame initially stratified by geographical region. Each stratum was then stratified by hospitals' main source of income (serving general public vs privately insured individuals) and ICU size (ten or fewer beds vs more than ten beds), finally generating 40 strata. In each stratum we selected a random sample of ICUs so as to enrol the total required beds in 1690 Brazilian adult ICUs. We followed up patients until hospital discharge censored at 60 days, estimated incidence from prevalence and length of stay, and generated national estimates. We assessed mortality prognostic factors using random-effects logistic regression models. Findings: On Feb 27, 2014, 227 (72%) of 317 ICUs that were randomly selected provided data on 2632 patients, of whom 794 had sepsis (30·2 septic patients per 100 ICU beds, 95% CI 28·4–31·9). The ICU sepsis incidence was 36·3 per 1000 patient-days (95% CI 29·8–44·0) and mortality was observed in 439 (55·7%) of 788 patients (95% CI 52·2–59·2). Low availability of resources (odds ratio [OR] 1·67, 95% CI 1·02–2·75, p=0·045) and adequacy of treatment (OR 0·56, 0·37–0·84, p=0·006) were independently associated with mortality. The projected incidence rate is 290 per 100 000 population (95% CI 237·9–351·2) of adult cases of ICU-treated sepsis per year, which yields about 420 000 cases annually, of whom 230 000 die in hospital. Interpretation: The incidence, prevalence, and mortality of ICU-treated sepsis is high in Brazil. Outcome varies considerably, and is associated with access to adequate resources and treatment. Our results show the burden of sepsis in resource-limited settings, highlighting the need to establish programmes aiming for sepsis prevention, early diagnosis, and adequate treatment. Funding: Fundação de Apoio a Pesquisa do Estado de São Paulo (FAPESP).